I'm bully-proof! a print production campainging against bullying in Mintal Elementary School - Gian, Justine Kate C.
Bullying, as considered as an emerging problem in schools around the globe, is also becoming a serious problem here in the Philippines. However, despite the high rate of bullying cases in schools in the Philippines, the efforts of the Department of Education were not enough to suffice for the requirements of the newly implemented law, the Anti-Bullying Law of 2012. This production thesis seeks to promote awareness on the issue of bullying and its negative impacts to schoolchildren. The researcher produced a series of posters that communicates the issue of bullying to the schoolchildren of Mintal Elementary School. Theories under Edutainment (Persuasion Theory and Social Learning Theory) and Visual Rhetoric were used as foundations of the content of the posters. Photographs were the main design element used in conveying the anti-bullying message. They show positive ways on how the schoolchildren could fight against bullying. Furthermore, the elements of design and principles of design and principles in children photography were used in designing the posters. In the entire production process, the researcher primarily considered her target audience. It was a challenge to make the posters visually attractive and comprehensible to the schoolchildren. The Four Principles for Communication for Children and the observation the researcher had were utilized to make the message relatable and identifiable to the children thus making the posters easy to understand.